Building Realist Program Theory for Large Complex and Messy Interventions. Issue 1 (27th November 2017) - Shearn, Katie; Allmark, Peter; Piercy, Hilary; Hirst, Julia
Program theory, that is, the specific idea about how a program causes the intended or observed outcomes, should be the central aspect of any realist evaluation or synthesis. The methods used for explicating or building initial rough program theories (IRPTs) in realist research are varied and arguably often underreported. In addition, preexisting psychological and sociological theories, at a higher level of abstraction, could be used to a greater extent to inform their development. This article illustrates a method for building IRPTs for use in realist research evaluation and synthesis. This illustration involves showing how the IRPTs were developed in a realist evaluation concerning sexual health services for young people. In this evaluation, a broad framework of abstract theories was constructed early in the process to support IRPT building and frame more specific program theories as they were developed. These abstract theories were selected to support theorizing at macro-, meso-, and microlevels of social structure. This article discusses the benefits of using this method to build initial theories for particular types of interventions that are large, complex, and messy. It also addresses challenges relating to the selection of suitable theories.